การสร้างอัตลักษณ์ของนักเรียนอาชีวศึกษาสายช่าง - ไปรยา ศรีสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To examine the identity of vocational students in the field of mechanics, and to investigate the factors influencing their self-perception and construction of their identity and how they are perceived by the public. To gather data, focus groups with vocational students and in-depth interviews with the general public were used. The results show that; 1) regarding individual identity, the vocational students were perceived differences in learning and lifestyle with general students, reflecting that there was no conflict with self-identity among the vocational students. The vocational students were perceived as troublemakers who are likely to be aggressive and commit violence. 2) social identity: individual vocational students have a somewhat different social identity. They are inclined to follow what seems suitable to them. Their expression and conduct was done through dress, wearing accessories symbolizing their institutes, respect for Vishnukarma, social dialect and public gathering mostly. 3) collective identity: vocational students are categorized by institution, and group formation; namely, learning groups and everyday lifestyle groups. Means of communication was expressed through dressing, social dialect, peer groups, education, educational advancement, values, belief, music, graffiti, love, drug use, extreme violence and quarreling. The factors influencing the identity construction of the vocational students included the student model, peers, senior students, family, vocational institute, related functional groups, mass media, and society. The identity formation process can be divided into two phrases, before and after becoming a vocational student The identity was formed through a process of nurturing the values and attitude, and imitation of senior students. The later perception varied with the context. The public perceived the vocational student’s identity through expression in public and their portrayal in the newspaper media mostly. The most frequently perceived picture of vocational students by the public was of violence, quarreling, gang activity and social problems.